OPTIMIZATION OF THE OPERATIONAL PARAMETERS FOR THE FURNACE OF A THREE BED REGENERATIVE OXIDIZER THAT NEUTRILIZES GASEUS POLLUTANTS - Pittas, Nicholas; Margaris, Dionissios; Georgiou, Demos (International Journal of Engineering Technologies and Management Research, 2018)
The purpose of this work is to correlate the excess oxidant-air with the percentage of CO2 in the combustion chamber waste gas of a three-bed regenerative thermal oxidizer unit for the elimination of gaseous pollutants in a given capacity.